Tourism management at UNESCO World Heritage Sites: The case of Angra do Heroísmo: the case of Angra do Heroísmo. - Dutra, Hagna; Lopes, Tiago; Silva, Francisco (Tourism and Hospitality International Journal, 2023)
The Autonomous Region of the Azores is characterized by strong insularity, small size, territorial dispersion, and limited accessibilities, which hinder its economic development. Due to its classification as a UNESCO World Heritage city (UWH), Angra do Heroísmo brings together opportunities for the development of cultural tourism at the regional level. This investigation aims to contribute to the analysis and understanding of the current management model of this classification, to guarantee the effective valuation of the heritage to be enhanced as a WHS, and to generate a greater qualification of its supply. For this purpose, in addition to contextual theoretical analysis, interviews were applied to stakeholders associated with the themes under study, which resulted in proposals for the effective valorization of the destination. It is concluded that the valuation of Angra do Heroísmo as a tourist destination requires a thorough understanding between entities, in particular, those operating within the classified area. Also, the development of a management and planning model seems crucial, so that strategic priorities on this particular WHS development are defined. In turn, these actions would be reflected throughout the region, reinforcing the identity and notoriety of the destination.